Antenatal screening for aneuploidy - Patne, Smita S.; Upadhye, Aditi J.; Shembekar, Shantanu C.; Shembekar, Chaitanya A.; Upadhye, Jayshree J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: It is uncertain how best to screen pregnant women for the presence of fetal Down's syndrome and other aneuploides, whether to perform first-trimester screening or to perform second-trimester screening or both. Methods: Women with singleton and multiple pregnancies underwent first-trimester combined screening (measurement of nuchal translucency, pregnancy-associated plasma protein A [PAPP-A], and the free beta subunit of human chorionic gonadotropin at 10 weeks 3 days through 13 weeks 6 days of gestation). Also, second-trimester quadruple screening (measurement of alpha-fetoprotein, total human chorionic gonadotropin, unconjugated estriol, and inhibin A) and triple marker test was done from 15 to 18 weeks of gestation. Results: 12 (5%) patients had positive screening test for combined screening in first trimester, 6 (10.9%) patients had positive screening for quadruple test while 1 (2.85%) patients had positive screening for triple test. Out of 19 positive screening, 16 (84.21%) had their amniocentesis done for confirmation of diagnosis. In all 16 patients, chromosomal analysis was normal. Not a single patient turned out to have a baby with Down syndrome or any other aneuploidy. False positive rate for combined screening in first trimester was 5%, false positive rate for quadruple test in second trimester was 10.9%, false positive rate for triple marker test in second trimester was 2.85%. Conclusions: First-trimester combined screening is better than second-trimester quadruple test or triple marker test for syndrome or any other aneuploidy.